Immune Checkpoint Modulators: An Emerging Antiglioma Armamentarium - Eileen S. Kim; Jennifer E. Kim; Mira A. Patel; Antonella Mangraviti; Jacob Ruzevick; Michael Lim (Journal of Immunology Research)
Immune checkpoints have come to the forefront of cancer therapies as a powerful and promising strategy to stimulate antitumor T cell activity. Results from recent preclinical and clinical studies demonstrate how checkpoint inhibition can be utilized to prevent tumor immune evasion and both local and systemic immune suppression. This review encompasses the key immune checkpoints that have been found to play a role in tumorigenesis and, more specifically, gliomagenesis. The review will provide an overview of the existing preclinical and clinical data, antitumor efficacy, and clinical applications for each checkpoint with respect to GBM, as well as a summary of combination therapies with chemotherapy and radiation.